VIRTUAL MUSEUM RESEARCH: A BIBLIOMETRIC MAPPING - Ramli, Siti Humaira; Ramlee, Siti Nurhafizah Saleeza; Johnny, Sudang; Hassan, Muhammad Zahiruddin (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2026)
The rapid advancement of immersive technologies has significantly transformed how cultural heritage is preserved, experienced, and disseminated through virtual museum platforms. Despite the growing scholarly interest, there remains a need to systematically map and analyze the intellectual structure and research trends in this emerging domain. This study addresses this gap by conducting a comprehensive bibliometric analysis of virtual museum research to uncover its key themes, influential contributors, and collaborative networks. Data were collected using Scopus advanced search with the keywords “Virtual Museums,” “Virtual VR,” and “Digital Heritage,” yielding a total of 844 documents. The dataset was cleaned and harmonized using OpenRefine to ensure consistency and accuracy. Statistical distributions and trend analyses were performed using Scopus Analyzer, while network visualizations were generated through VOSviewer software to explore co-authorship, co-occurrence of keywords, and country collaborations. The findings reveal a steady increase in publications over the past decade, with significant contributions from China, Italy, and the United Kingdom as leading research hubs. Keyword co-occurrence analysis identified dominant themes such as virtual reality, cultural heritage preservation, interactive experiences, and educational applications. Nine country collaboration clusters were detected, highlighting the global and interdisciplinary nature of this field. Overall, the study provides a structured overview of the knowledge landscape, identifies research hotspots, and highlights emerging directions for future work in virtual museum research. These insights not only contribute to the theoretical development of digital heritage studies but also inform practical strategies for enhancing cultural access, preservation, and innovation through technology.